2010
DOI: 10.19173/irrodl.v11i1.775
|View full text |Cite
|
Sign up to set email alerts
|

Learning in an online distance education course: Experiences of three international students

Abstract: This case study explores the learning experiences of three international students who were enrolled in an online master's program offered by a large university in Canada. The aim of the study was to understand the international students' experiences with, and perspectives on, the online learning environment. Findings indicate that previous education and especially language proficiency strongly impacted the learning of these students in this environment. Non-native English speakers required considerably more ti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
40
0
4

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 82 publications
(45 citation statements)
references
References 33 publications
1
40
0
4
Order By: Relevance
“…Οι δύο μεταβλητές του μοντέλου αυτού είναι η αντιληπτή χρησιμότητα και η αντιληπτή ευκολία χρήσης (Halawi & McCarthy, 2008;Ngai, Poon & Chan, 2007;Johnson, Hornik & Salas, 2008). Τέλος, μία ακόμα σημαντική παράμετρος η οποία σχετίζεται με την παρούσα έρευνα είναι η ετοιμότητα στη χρήση της γλώσσας επικοινωνίας (Mason & Gunawardena, 2001;Bates, 2001;Goodfellow, Lea, Gonzalez & Mason, 2001;Zhang & Kenny, 2010). Εκτός από τις παραπάνω παραμέτρους που εξ αρχής κρίθηκε σκόπιμο να διερευνηθούν, στην πορεία της παρούσας έρευνας ως σημαντικές αναδείχθηκαν δύο ακόμη παράμετροι: α) η ενεργητική συμμετοχή των εκπαιδευομένων στις διάφορες δραστηριότητες και β) τα στοιχεία της προσωπικότητάς τους και οι ατομικές στρατηγικές μάθησης που εφαρμόζουν.…”
Section: εισαγωγήunclassified
See 1 more Smart Citation
“…Οι δύο μεταβλητές του μοντέλου αυτού είναι η αντιληπτή χρησιμότητα και η αντιληπτή ευκολία χρήσης (Halawi & McCarthy, 2008;Ngai, Poon & Chan, 2007;Johnson, Hornik & Salas, 2008). Τέλος, μία ακόμα σημαντική παράμετρος η οποία σχετίζεται με την παρούσα έρευνα είναι η ετοιμότητα στη χρήση της γλώσσας επικοινωνίας (Mason & Gunawardena, 2001;Bates, 2001;Goodfellow, Lea, Gonzalez & Mason, 2001;Zhang & Kenny, 2010). Εκτός από τις παραπάνω παραμέτρους που εξ αρχής κρίθηκε σκόπιμο να διερευνηθούν, στην πορεία της παρούσας έρευνας ως σημαντικές αναδείχθηκαν δύο ακόμη παράμετροι: α) η ενεργητική συμμετοχή των εκπαιδευομένων στις διάφορες δραστηριότητες και β) τα στοιχεία της προσωπικότητάς τους και οι ατομικές στρατηγικές μάθησης που εφαρμόζουν.…”
Section: εισαγωγήunclassified
“…Όσον αφορά την επίδραση της ενεργής συμμετοχής στο βαθμό ικανοποίησης, από τους 11 μαθητές που φάνηκαν πολύ ικανοποιημένοι από τη συνεργασία eTwinning οι 9 είχαν συμμετάσχει ενεργά και με προθυμία (οι τέσσερις μάλιστα με μεγάλο ενθουσιασμό) σε όλες τις δραστηριότητες της συνεργασίας. Το γεγονός αυτό δείχνει ότι η ενεργή συμμετοχή, η οποία σύμφωνα με τους ερευνητές (Harasim et al, 1995;Zhang & Kenny, 2010) παίζει σημαντικό ρόλο στην εξ αποστάσεως εκπαίδευση, επηρεάζει σημαντικά και το βαθμό ικανοποίησης. Σύμφωνα με την Arbaugh (2000), οι πιο ενδεδειγμένες παιδαγωγικές πρακτικές για την εκπαίδευση μέσω διαδικτύου είναι αυτές που ενισχύουν την ενεργητική μάθηση και την αλληλεπιδραστικότητα (interactivity).…”
unclassified
“…Furthermore, Zhang and Kenny (2001) maintained that in an online classroom, students are more prone to be easily distracted because they are at home. They may be distracted by personal phone calls, chores, TV or even roommates (Kenny & Zhang, 2010). Wenden (1991) suggested that in an online course there is no assurance that a student is paying full attention to the lesson at hand.…”
Section: Second Language Learningmentioning
confidence: 99%
“…These institutions need to consider the learning needs of all students, including English language learners, who choose to take online courses. In a study of three international students' experiences in distance learning at a four year institution, Kenny and Zhang (2010) found that some of the participants were reluctant to engage in course discussions because they were not sure what they could contribute. These students were not from North America and lacked background knowledge.…”
Section: Distance Learning and International Ellsmentioning
confidence: 99%
“…Various scholars (e.g. Higgins, 1998;Moore & Kearsley, 2005;Peters, 2010;Zhang & Kenny, 2010) argued that online education has shifted the focus from knowledge transmission to knowledge constructing and the role of the teacher from knowledge transmitter to that of a facilitator who provides considerable opportunities for interaction and meaningmaking to distant learners. Indeed, online learning has become a new paradigm for teaching and learning given the capability of expanding ICTs and the widespread concepts of constructivist-oriented open and distance life-long learning.…”
Section: Introductionmentioning
confidence: 99%